2017
DOI: 10.1002/cjoc.201700280
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Rearrangement of Isatins with Arylamines Using H2O2 as Oxidant: A Facile Synthesis of Quinazoline‐2,4‐diones and Evaluation of Their Antibacterial Activity

Abstract: A green and highly efficient synthetic method for the synthesis of quinazoline‐2,4‐diones with hydrogen peroxide as the terminal oxidant has been developed. The reaction features the mild reaction conditions, broad substrate scope, metal‐free catalysts, and sole byproduct water. A plausible mechanism for this process was proposed. Moreover, an antibacterial activity study was performed to evaluate the antimicrobial activities towards two Gram‐negative bacterial strains (Escherichia coli, and Klebsiella pneumon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…59 The title compound was synthesized according to the general procedure and obtained as a white solid (35.3 mg, 70%); 3:7 (EA/Hexane) as the eluent; 1 H-NMR (400 MHz, DMSO-d 6 ) 11.52 (s, 1H), 7.93 (dd, J = 8.0 Hz, 1.4 Hz, 1H), 7.69 (td, J = 8.0 Hz, 1.2 Hz, 1H), 7.28−7.17 (m, 6H), 2.37 (s, 3H); 13 3-(4-Ethylphenyl)quinazoline-2,4(1H,3H)-dione (2c). 60 The title compound was synthesized according to the general procedure and obtained as a white solid (35.6 mg, 67%); 3:7 (EA/Hexane) as the eluent; 1 H-NMR (400 MHz, DMSO-d 6 ) δ 11.53 (s, 1H), 7.94 (dd, J = 8.0 Hz, 1.6 Hz, 1H), 7.70 (td, J = 8.0 Hz, 1.2 Hz, 1H), 7.33−7.30 (m, 2H), 7.25−7.19 (m, 4H), 2.67 (q, J = 8.0 Hz, 2H), 1.24 (t, J = 8.0 Hz, 3H). 13 3-(4-Methoxyphenyl)quinazoline-2,4(1H,3H)-dione (2d).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…59 The title compound was synthesized according to the general procedure and obtained as a white solid (35.3 mg, 70%); 3:7 (EA/Hexane) as the eluent; 1 H-NMR (400 MHz, DMSO-d 6 ) 11.52 (s, 1H), 7.93 (dd, J = 8.0 Hz, 1.4 Hz, 1H), 7.69 (td, J = 8.0 Hz, 1.2 Hz, 1H), 7.28−7.17 (m, 6H), 2.37 (s, 3H); 13 3-(4-Ethylphenyl)quinazoline-2,4(1H,3H)-dione (2c). 60 The title compound was synthesized according to the general procedure and obtained as a white solid (35.6 mg, 67%); 3:7 (EA/Hexane) as the eluent; 1 H-NMR (400 MHz, DMSO-d 6 ) δ 11.53 (s, 1H), 7.94 (dd, J = 8.0 Hz, 1.6 Hz, 1H), 7.70 (td, J = 8.0 Hz, 1.2 Hz, 1H), 7.33−7.30 (m, 2H), 7.25−7.19 (m, 4H), 2.67 (q, J = 8.0 Hz, 2H), 1.24 (t, J = 8.0 Hz, 3H). 13 3-(4-Methoxyphenyl)quinazoline-2,4(1H,3H)-dione (2d).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Common methods for the ring-expansion reaction of isatins and their derivatives are as follows: 1) ring-expansion through the cleavage of the C2-N1 bond with enamines to synthesize multisubstituted quinoline-4-carboxamides derivatives; [6] 2) ring-formation through the insertion of atoms into the C2-C3 or C3-C4 bond. [7] For example, Zou and co-workers reported an efficient and practical method for the construction of benzimidazo[l,2-c]quinazolin-6ones through the cleavage of the C2-C3 bond and insertion of heteroatoms using molecular oxygen as the oxidant.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Quinazoline-2,4-diones are also important intermediates for preparation of some important drugs under chemo selective reactions, [7,8] In literature, several methods are reported for preparation of quinazoline-2,4-diones. For example, by reductive cyclization of o-nitro benzamides and triphosgene under titanium catalylsis; [9] by base mediated condensation of 2-aminobenzamides and di-tert-butyl dicarbonate; [10] selenium-catalyzed carbonylation of o-nitrobenzamides; [11] by base mediated oxidative rearrangement of arylamines with isatins; [12] by palladiumcatalyzed arylation ester-amidation sequence to produce quinazolinedione derivatives; [13] by cyclocarbonylation of 2iodoanilines with heterocumulenes underpalladium acetate catalysis; [14] ZnCl 2 mediated condensation of aromatic o-aminonitriles with DMF or N,N-diethylformamide. [15] Oxidative rearrangement reactions can serve as effective tools for the blend of two heterocyclic-containing moieties, tert-Butyl hydroperoxide (TBHP) has recently been utilized as an attractive and environmentally benign oxidant in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…[26] Earlier, Shang et al, reported synthesis of quinazolinediones by reaction of isatins with arylamines in the presence of base such as sodium bicarbonate using H 2 O 2 as oxidant. [12] In this approach, stoichiometric quantity of a base (1.2 equiv.) and oxidant H 2 O 2 (3 equiv.)…”
Section: Introductionmentioning
confidence: 99%